Cutaneous manifestations of juvenile onset lupus erythematosus: A clinical study - Vinitha Panicker; Anil Mathew; Gopikrishnan Anjaneyan; Soumya Jagadeesan; S. Lekshmi; Jacob Thomas (Indian Journal of Paediatric Dermatology, 2018)
Introduction: Juvenile-onset systemic lupus erythematosus (SLE) is one of the most common systemic autoimmune connective tissue disorders in children. Studies focusing on the mucocutaneous manifestations of childhood lupus are scanty in literature. Objectives: This study was an attempt to describe the cutaneous changes seen in Pediatric Lupus and to correlate with the histopathological and immunofluoresecence findings. Methods: This was a retrospective study. All children under the age of 18 years who were diagnosed to have SLE according to the ACR criteria and presented to the dermatology outpatient department during a period of 1 year were included in the study. Details including clinical features, investigation findings including immunological tests and skin biopsy findings were noted. The analysis was performed using descriptive statistical tools such as percentage and frequency. Results: A total of 14 cases, average age at presentation was 10.14 years. Among the cutaneous manifestations, the most common presenting feature was urticarial vasculitis. Malar rash was seen in 57% of cases. Other cutaneous features seen were diffuse alopecia, oral ulcers. Antinuclear antibody was positive in all cases. Conclusion: Pediatric lupus tends to have a more aggressive course than adult lupus. Early diagnosis and treatment is necessary to prevent progression and development of complications.